2008
DOI: 10.1021/jp711193u
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Optical Response of Polyethylene Films Containing Luminescent Perylene Chromophores

Abstract: In this work, two perylene derivatives containing different peripheral alkyl chains (i.e., N,N'-bis-(hexyl)perylene-3,4,9,10-tetracarboxyldiimide (ES-PTCDI) and N,N'-bis-(2'-ethylhexyl)perylene-3,4,9,10-tetracarboxyldiimide (EE-PTCDI)) were synthesized and efficiently dispersed at low loadings (from 0.01 to 0.1 wt %) into linear low-density polyethylene (LLDPE) by processing in the melt. Spectroscopic investigations (UV-vis and fluorescence) combined with quantum-mechanical studies demonstrated the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
121
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 42 publications
1
121
0
Order By: Relevance
“…We have shown that this general concept of stimulus-triggered dye (dis)assembly in polymer matrices allows for the design of a broad range of sensor materials, which are useful for the detection of temperature history, [13][14][15][16][17] exposure to chemicals, [18,19] and mechanical deformation, [20][21][22][23][24] as well as more complex combinations of stimuli, such as seen in shape-memory materials. [25] Others have adapted the concept and extended it to a range of dyes including cyano containing poly(phenylene ethynylenes), [26] perylenes, [27] CdS nanoparticles, [28] and bis(benzoxazolyl)stilbenes. [29] The temperature and humidity sensors based on such polymer/dye blends operate by kinetically trapping a thermodynamically unstable molecular mixture of the components by rapidly cooling a hot (and at this temperature miscible) mixture below its glass transition temperature (T g ).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that this general concept of stimulus-triggered dye (dis)assembly in polymer matrices allows for the design of a broad range of sensor materials, which are useful for the detection of temperature history, [13][14][15][16][17] exposure to chemicals, [18,19] and mechanical deformation, [20][21][22][23][24] as well as more complex combinations of stimuli, such as seen in shape-memory materials. [25] Others have adapted the concept and extended it to a range of dyes including cyano containing poly(phenylene ethynylenes), [26] perylenes, [27] CdS nanoparticles, [28] and bis(benzoxazolyl)stilbenes. [29] The temperature and humidity sensors based on such polymer/dye blends operate by kinetically trapping a thermodynamically unstable molecular mixture of the components by rapidly cooling a hot (and at this temperature miscible) mixture below its glass transition temperature (T g ).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the polymer matrix to break up these aggregates was found to be mainly determined by the dye aggregate size, the crystallinity of the polymer matrix, and the strain rate. Hydrophobically modified perylene derivatives were also found to be suitable candidates for forming aggregates in poly(ethylene) matrices that are responsive to mechanical stimuli [50].…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…While the study did also not involve well-defined supramolecular assemblies, the results paved the way for subsequent work on mechanochromic polymers comprising assemblies of aggregachromic, excimer-forming cyano-substituted oligo(p-phenylene vinylene)s (cyano-OPVs, Figures 2-4). [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Scanning confocal microscopy images of blend films of ultra-high-molecular-weight polyethylene and 10 -4 % w/w EHO-OPPE (Figure 1). a) As prepared film.…”
Section: π-π Interactionsmentioning
confidence: 99%
“…Similar changes in absorption have also been reported for a PETG-based polymer films in which a cyano-OPV dye was covalently introduced into polymer chain. [45] Pucci and coworkers have also reported LLDPE-based films containing perylene bisimide derivatives, [54] which have been intensively examined because of their attractive optoelectronic character and propensity to assemble into supramolecular architectures. Blend films comprising N,N'-bis-(2'-ethylhexyl)perylene-3,4,9,10-tetracarboxyldiimide (EE-PTCDI) in LLDPE were obtained by melt-mixing procedures and blend films with 0.1% w/w of the dye exhibited mechanoresponsive behavior as shown in Figure 10.…”
Section: π-π Interactionsmentioning
confidence: 99%